Influence of Melt Supply on the Spreading State of a Slow–Ultraslow-Spreading Ridge: The Reykjanes Ridge, North Atlantic - Lihong Zhao; Yingzi Liu; Zilong Ling; Pengyao Zhi; Faqiang Zhao; Hongqin Liu; Jinwei Zhang (Journal of Marine Science and Engineering, 2024)
Although recent research suggests that the morphology and crustal structure of slow–ultraslow-spreading ridges are mainly controlled by melt supply, there is a lack of quantitative understanding of the effect of systematic changes in melt supply on the seafloor spreading state of mid-ocean ridges. In this study, we used bathymetry, free-air gravity anomaly, and sediment thickness data to calculate the residual bathymetry, mantle Bouguer gravity and crustal thickness of the Reykjanes Ridge. According to the gradient of changes in crustal thickness and residual bathymetry along the axis, the influence of melt supply on the spreading state of the Reykjanes Ridge can be divided into three zones: ultra-strong effect zone (0–160 km), strong effect zone (160–610 km), and weak effect zone (610–930 km). In the ultra-strong effect zone, excess melt supply and a higher melting degree result in a strong upwelling and large melt eruption. The change in relative position between the Reykjanes Ridge and the Iceland hotspot results in the spreading state of the Reykjanes Ridge transforming from asymmetric spreading to symmetric spreading. In the strong effect zone, the decrease in melt supply and melting degree weakens the mantle upwelling and enhances the viscosity of the dehydrated mantle layer. Sufficient viscosity of the dehydrated mantle layer forces asymmetric asthenosphere rise along the sloping boundary of the lithosphere, resulting in symmetric spreading. In the weak effect zone, the pattern of magma upwelling becomes a focused magma supply pattern similar to that of the slow–ultraslow-spreading of the mid-ocean ridge, and tectonics dominate the spreading process. The asymmetry of this weak effect zone may be due to the concentration of tectonic and magmatic activity on one flank of the ridge.